Disorders of nail in infants and children - Archana Singal; Kavita Bisherwal (Wolters Kluwer Medknow Publications, 2019)
Nail disorders in infants and children do not contribute to substantial pediatric consultations as they are relatively uncommon. Nail changes are often missed as specific nail examination is not routinely done in this age group. The presentation and management of nail disorders in children are different from adults; few being specific to the children. Physiological alterations are common in infants and pediatric age. These should be known to a clinician so as to differentiate from pathological conditions, to reassure parents, and to avoid unnecessary medical intervention. The congenital nail disorders can be a part of major hereditary syndromes requiring further evaluation. Several acquired causes may cause nail dystrophy. Some of them are self-limiting while others may require long-term management. Meticulous and careful nail examination is, therefore, important in neonates, infants and children for early diagnoses, management and to prevent complications. There are few epidemiological studies delineating nail changes in infants and children. In this script, we have comprehensively reviewed nail conditions seen in pediatric population through all stages, i.e., neonates, infants, and children.